Scaling Up Community-Driven Development : Theoretical Underpinnings and Program Design Implications - Binswanger, Hans P.; Aiyar, Swaminathan (World Bank, Washington, DC, 2014)
Community-driven development boasts many islands of success, but these have not scaled up to cover entire countries. Binswanger and Aiyar examine the possible obstacles to scaling up, and possible solutions. They consider the theoretical case for community-driven development and case studies of success in both sectoral and multisectoral programs. Obstacles to scaling up include high economic and fiscal costs, adverse institutional barriers, problems associated with the co-production of outputs by different actors on the basis of subsidiarity, lack of adaptation to the local context using field-tested manuals, and lack of scaling-up logistics. The authors consider ways of reducing economic and fiscal costs, overcoming hostile institutional barriers, overcoming problems of co-production, adapting to the local context with field testing, and providing scaling-up logistics. Detailed annexes and checklists provide a guide to program design, diagnostics, and tools.